Numerical modeling of groin impact on nearshore hydrodynamics - Rocha, M. (2013)
Groins are cross shore structures built to promote shoreline stabilization. However, the specific impact of these structures on the wave conditions and velocity field nearshore (and hence, on sediment transport) is still poorly understood. Therefore, this study wishes to extend this knowledge using a numerical model, COULWAVE, previously validated with field data. For that, a typical bar-trough profile is considered and different groin lengths and orientations are tested, under the influence of different significant incident-wave heights and sea-surface levels. The hydrodynamics factors are found to have a greater impact on the nearshore wave conditions than the groin geometry. The variation of significant incident-wave height imparts the greater changes in wave height nearshore, where the groin would be located. The typical tidal range is also important, since a 2 m change in sea surface level can cause great depth changes over bathymetric features and thus influence wave propagation. Although less important, the geometry of the groin should also be considered. The greater the length, the greater the sheltering effect expected, extending further to the lee-side of the groin. The impact will also reach a broader region. With a smaller impact verified, the best orientation of the groin is hard to unravel.